Introduction to inmarsat broadband global area network for mobile backbone networks - Stojce Dimov Ilcev (Bulletin of Electrical Engineering and Informatics, 2020)
In this paper is introduced the Inmarsat Global Area Network (GAN) as backbone to mobile networks. At the end of 2005 Inmarsat launched its BGAN service as the first high speed wireless data solutions with voice available on a global basis. The service is accessed through a portable, broadband satellite transceiver with antenna easy to carry as a laptop. The BGAN network consists constellation of Geostationary Earth Orbit (GEO) I-4 and I-5 satellites with an optimized ground network, which interconnects variety of terrestrial infrastructures at local BGAN users. This system employs bandwidth efficient modulation and coding techniques, capable of supporting variable bit-rate services and QoS depending on the needs of the application. The BGAN system is satellite component of 3G IMT-2000, specially the Universal Mobile Telecommunications Service (UMTS) standards. It will provide a near-global coverage overlay for the terrestrial networks, giving users service availability beyond the reach of terrestrial IMT-2000 networks. A range of supported terminals, personal devices, portable and mobile units linked with onboard entertainment, communications systems to remote base stations for civilian and military applications and SCADA or M2M are discussed.